2011
DOI: 10.1103/physreva.84.053408
|View full text |Cite
|
Sign up to set email alerts
|

High degree of molecular orientation by a combination of THz and femtosecond laser pulses

Abstract: We propose a method for achieving molecular orientation by two-step excitation with intense femtosecond laser and terahertz (THz) pulses. First, the femtosecond laser pulse induces off-resonant impulsive Raman excitation to create rotational wave packets. Next, a delayed intense THz pulse effectively induces resonant dipole transition between neighboring rotational states. By controlling the intensities of both the pulses and the time delay, we can create rotational wave packets consisting of states with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 35 publications
(40 reference statements)
6
83
0
Order By: Relevance
“…Note that a larger degree of orientation can be achieved with the two-color mechanisms through ionization depletion [53]. In this second regime, molecular orientation has been recently addressed experimentally for linear molecules using only a THz field [54] or its combination with a laser field [55], and in [56,57] for an excitation process with two-color laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…Note that a larger degree of orientation can be achieved with the two-color mechanisms through ionization depletion [53]. In this second regime, molecular orientation has been recently addressed experimentally for linear molecules using only a THz field [54] or its combination with a laser field [55], and in [56,57] for an excitation process with two-color laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…One numerical study reported a high degree of orientation (>0. 8) (low-temperature limit) [34] with experimentally available conditions. In the recent experiment by Egodapitiya et al [36], the effectiveness of the introduction of a pre-laser pulse prior to a near-single-cycle THz pulse was confirmed, in which the degree of orientation is similar in value to that achieved by the two-color scheme but is obtained with avoiding ionization.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have introduced a pre-laser pulse to prepare an aligned superposition state and applied a near-single-cycle THz pulse to this state with a suitable time delay [34][35][36]. One numerical study reported a high degree of orientation (>0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations show that waveform-controlled THz radiation is of great importance due to its potential application in THz imaging and coherent control of molecular dynamics [25,26]. Can we control the waveform of femtosecond laser filament based THz radiation?…”
Section: Introductionmentioning
confidence: 99%